The 13th footprint. 1 - Sanbe, Kei (Yen Press, 2025)
After Touya and Haru's son, Ao, was released from the hospital, the Togawa family was ready for a fresh start in their picturesque new home. But the life Touya envisioned for his family is turned upside down when mysterious postcards begin to appear. No sender, no return address-just a note describing an event that will happen in the future! Following the prophetic cards, Touya embarks on an adventure to help those in need, keep his family safe, and unravel the mystery before disaster catches up with them...